Cryopreservation of somatic germplasm of selected Australian monocotyledonous taxa (Haemodoraceae). - Turner, Shane (Curtin University, 2001)
The South West Botanical Province of Western Australia is one of the most floristically rich areas of the world with over, 8,000 species present, the majority of which (70%), are endemic to this region. Coupled with this high level of endemism, many taxa are threatened which makes them vulnerable to habitat alterations, modifications and destruction. Significant habitat alteration in many areas has resulted in 27 species becoming extinct in the South West Botanical Province, while an additional 327 species are classified as rare and endangered. In the context of stemming this loss of biodiversity, research in cryopreservation was undertaken to provide offsite protection and conservation of somatic germplasm.Cryostorage techniques were evaluated in this study to determine the key factors which may affect the ability of somatic tissues of Haemodoraceae species to survive, recover and grow following liquid nitrogen (LN) immersion and storage. Using Anigozanthos viridis as a comparator in most experiments, the base vitrification protocol was established, which involved: (1) preculturing shoot apices on 0.4 M sorbitol for 48 h; (2) incubation in a vitrification cryoprotective solution (PVS2) for 25 min at 0 degrees celsius; (3) LN immersion; (4) recovery to active growth through warming (immersion in a 40 degrees celsius water bath). Using this procedure the highest post-LN survival of shoot apices for A. viridis was 41.4 plus or minus 6.1% Four additional taxa were successfully cryopreserved with this base protocol (Anigozanthos manglesii, A. rufus, Conostylis wonganensis and A. rufus x A. pulcherrimus); a fifth taxon, Macropidia fuliginosa, however, proved unresponsive.To improve on post-LN survival, further research established that four of the six study taxa responded to the following amendments to the basic protocol: (1) longer preculture duration; (2) preculture on 0.8 M glycerol rather than sorbitol, (3) utilisation of PVS2 solutions with reduced DMSO content; and (4) incorporation of an additional loading phase (2 M glycerol plus 0.4 M sucrose for 20 mins at 0 degrees celsius).Macropidia fuliginosa, a species with poor recovery after LN exposure, was successfully cryostored using somatic embryos. Treatments which resulted in the highest survival (67.3% 5.7 plus or minus %) included preculture with 0.4 M sorbitol, and incubation in PVS2 for 30 min. Further experimentation indicated that preculture for two days on 0.8 M glycerol (replacing 0.4 M sorbitol) was more beneficial for achieving high post-LN survival.Post-LN survival was significantly correlated to the use of polyalcohols when the total number of hydroxyl (-OH) groups (regardless of molarity) present was the same as that found in 0.4 M sorbitol. It was hypothesised that hydroxyl number is more important than molarity in membrane stabilisation, during dehydration and cooling. Post-LN survival was also found to be significantly influenced by stereochemical arrangement of the -OH groups of polyalcohol molecules used in the preculture media. Finally, post-LN survival was also found to be significantly influenced by the size of the molecule, with smaller polyalcohols with more -OH groups on one flank of the carbon chain being superior as cryoprotective agents.The influence of plant growth regulators on post-LN survival and recovery growth was also investigated. The survival of shoot apices was not correlated to cytokinin or auxin treatments administered in culture media prior to cryostorage. However, in the recovery medium, a combination of cytokinin and 0.5 mu M GA(subscript)3 in the medium was found to be the most efficacious for obtaining healthy plantlets.Genetic fidelity was then examined using Amplified Fragment Length Polymorphism (AFLP). Plantlets of one done kept or maintained under the following conditions: (1) standard tissue culture conditions; (2) cold storage and (3) cryostorage, over a 12 month duration, showed no detectable genetic changes.Further, shoot apex viability evaluated at regular intervals (after 0, 3, 6 and 12 months of LN storage) suggested that medium term storage of samples cryopreservation did not reduce shoot apex viability over this time span.This study has provided a better understanding of the factors influencing post-LN survival and recovery and, as a result, the cryopreservation protocols have been refined. Consequently, the prospects for conserving threatened Haemodoraceae species from Western Australia through cryostorage is now significantly improved.